2018
DOI: 10.1007/s10286-018-0504-4
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic function testing in spinocerebellar ataxia type 2

Abstract: PurposeTo assess whether autonomic failure belongs to the clinical spectrum of spinocerebellar ataxia type 2 (SCA2), an autosomal dominant genetic disorder showing progressive cerebellar and brainstem dysfunction.MethodsWe evaluated cardiovascular autonomic function in 8 patients with SCA2 and 16 age- and gender-matched healthy controls. Other autonomic domains were examined through standardized questionnaires and by testing the skin sympathetic reflex.ResultsPatients with SCA2 showed normal responses to cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…CAFTs allow the detection of orthostatic hypotension (OH), namely a sustained BP drop ≥ 20 mmHg systolic or ≥ 10 mmHg diastolic or an absolute systolic BP value < 90 mmHg after 3 min of head-up tilt or active standing, and ascertain its neurogenic origin [11,12]. Hereditary cerebellar ataxias and SAOA may experience various autonomic symptoms [7,13,14], but orthostatic hypotension is rare [15] and its detection enables the diagnosis of "possible MSA-C", according to international criteria [6]. A severe orthostatic hypotension, namely a BP fall > 30 mmHg systolic or > 15 mmHg diastolic is required to diagnose "probable" MSA-C [6].…”
Section: Introductionmentioning
confidence: 99%
“…CAFTs allow the detection of orthostatic hypotension (OH), namely a sustained BP drop ≥ 20 mmHg systolic or ≥ 10 mmHg diastolic or an absolute systolic BP value < 90 mmHg after 3 min of head-up tilt or active standing, and ascertain its neurogenic origin [11,12]. Hereditary cerebellar ataxias and SAOA may experience various autonomic symptoms [7,13,14], but orthostatic hypotension is rare [15] and its detection enables the diagnosis of "possible MSA-C", according to international criteria [6]. A severe orthostatic hypotension, namely a BP fall > 30 mmHg systolic or > 15 mmHg diastolic is required to diagnose "probable" MSA-C [6].…”
Section: Introductionmentioning
confidence: 99%
“…There is no significant correlation with CAG repeat length [9]. Autonomic neurophysiologic evaluation usually unveil urinary, gastrointestinal, and sweat dysfunction, while cardiac neuropathy abnormality is controversial [17].…”
Section: Spinocerebellar Ataxias (Autosomal Dominant)-scasmentioning
confidence: 99%
“…Interestingly, earlier reports indicated that cardiovascular autonomic failure with OH may be found in up to 25% people with SCA 3 mutations, with one study also reporting cardiac sympathetic denervation at 123 I-MIBG-SPECT [91,92]. At present, neurogenic OH seems to yield a limited diagnostic accuracy for distinguishing MSA-C from autosomal dominant cerebellar ataxia, particularly SCA 3 and 17, but further studies in larger independent cohorts with combined CAFT and cardiac 123 I-MIBG-SPECT are needed to clarify this issue [34,76,[89][90][91][92]. Whereas it is not generally recommended to perform genetic testing in individuals with clinically established MSA [4], this may be considered in case of positive family history, isolated cerebellar atrophy at neuroimaging or mild, non-progressive forms of autonomic failure [88,89].…”
Section: Cerebellar Ataxiamentioning
confidence: 99%